Effect of back massage on pain perception during first stage of labor among primi mothers in a teaching hospital - Karki, Pratiksha (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Labor pain is experienced and endured by every childbearing woman, and pain relief measures are often neglected. Thus, this study aimed to identify the effect of back massage on pain perception during the first stage of labor among primi mothers at Patan Hospital. Method: A quasi experimental study was conducted among 56 primi mothers (28 experimental and 28 control groups) selected purposively in the active room of the maternity ward. Mothers who met the inclusion criteria were assigned non-randomly into experimental (received usual labor care and mustard oil back massage) and control groups (received usual labor care). The Visual Analogue Scale (VAS) was used to assess labor pain before and after 15 minutes of intervention in both groups, and the data was analyzed by descriptive and inferential statistics using SPSS version 16 software. Result: The mean score of pain perceived by mothers before intervention in the experimental group was 68.21 mm, and the control group was 69.39 mm. There was a significant difference in pain perception before and after back massage in the experimental group (p<0.001). Similarly, a significant difference was found after intervention in the experimental and control groups (p<0.001). Conclusion: Back massage was effective in reducing labor pain. The findings of the study might be helpful to those planning to include labor pain relief measures in maternity wards.